Prevalence of STIs, sexual practices and substance use among 2083 sexually active unmarried women in Lebanon - Sara Abu Zaki (Nature Portfolio, 2021)
Abstract Access to sexual and reproductive health in conservative communities and in the MENA region are particularly limited and, as such, increase women’s vulnerability to unwanted pregnancies, unsafe abortions, and sexually transmitted infections (STIs). The aim was to assess the prevalence of STIs, sexual practices, recreational drug-use and their possible associations among cisgender unmarried women residing in Lebanon. Data on demographics, sexual practices and substance-use were collected from 2083 unmarried cisgender women who voluntarily attended a sexual health clinic in Lebanon between 2015 and 2019. They tested for HIV, Hepatitis B, Hepatitis C and Syphilis through rapid testing. Other infections (genital warts, Neisseria gonorrhea/Chlamydia trachomatis) were screened for. Regression models were computed between variables. There were two cases of HIV, one of Hepatitis B and syphilis, and no cases of Hepatitis C. Genital warts were present in 15% and symptoms indicative of Neisseria gonorrhea/Chlamydia trachomatis in 14%. Inconsistent condom-use (81%) was significantly associated with number of partners (adj. OR: 0.4). Inconsistent condom-use discussion with partners (33%) was significantly associated with unemployment (adj OR: 1.7), recreational drug-use (adj. OR: 1.4), and number of partners (adj. ORs 3.7–4.4). Unwanted pregnancies (11%) were significantly associated with age (adj. ORs 0.1–0.37), recreational drug-use (adj. OR: 2), using intrauterine device (adj. OR:2.9) and natural birth control methods (adj. OR: 2.4). Recreational drug-use (33%) was significantly associated with age (adj ORs 1.9–2.2), and smoking status (adj. OR: 0.6). The results indicate an urgent need for: (1) Accessible, non-stigmatizing, and inclusive sexual health services dedicated to women’s sexual health; (2) Comprehensive and non-stigmatizing sexual health education for all, but especially women, in order to promote safer sexual practices and effective decision making with regards to contraception and condom-use.